Organometallic Compounds - Green, M. L. author. aut Link
XIII, 376 p. 138 illus.
Keywords: to thank Messrs J. R. Sanders, W. E. Lindsell and M. G. Swanwick for helping to check the text and references and prepare indexes. Finally, I should like to thank my wife for the very considerable assis tance she has given me in the writing and production of this book. M. L. H. G. Contents Preface to the Third Edition, Volume Two Page v INTRODUCTION TO VOLUME TWO I Oassification I The IS-electron rule 2 (i) The basis of the I8-electron rule p. 4, (ii) Exceptions to the I8-electron rule p. 5 1. TWO-ELECTRON LIGANDS 7 A. Classification 7 B. The preparation of olefin-transition metal complexes 7 (a) Displacement of solvent ligands p. 9, (b) Preparations from metal carbonyls p. 9, (c) Less common preparative routes p. 11, Reductive olefination method p. 12 C. A molecular orbital description of the bonding in orga- metallic complexes 13 (a) General comments p. 13, (b) Symmetry considerations p. 13, (c) Energies of the molecular orbitals p. 14 D. A description of the bonding of 2-electron ligands to transition metals 14 E. General comments of 2-electron ligands 19 (a) Infrared studies p. 20, (b) Effect of olefin substituents p. 21, (c) The rotation of ethylene about the ligand-metal bond p. 22, (d) Chemical properties p. 23 F. Particular complexes of metals with 2-electron ligands 25 (a) Copper, silver and gold p. 25, Complexes with benzene p. 28, (b) Nickel, palladium and platinum p.